Error-Related Activity and Correlates of Grammatical Plasticity - Davidson, Doug; Indefrey, Peter (Frontiers in Psychology, 2011)
Cognitive control involves not only the ability to manage competing task demands, but also the ability to adapt task performance during learning. This study investigated how violation-, response-, and feedback-related electrophysiological (EEG) activity changes over time during language learning. Twenty-two Dutch learners of German classified short prepositional phrases presented serially as text. The phrases were initially presented without feedback during a pre-test phase, and then with feedback in a training phase spanning two days spaced one week apart. The stimuli included grammatically correct phrases, as well as grammatical violations of gender and declension. Without feedback, participants' classification was near chance and did not improve over trials. During training with feedback, behavioral classification improved and violation responses appeared to both types of violation in the form of a P600. Feedback-related negative and positive components were also present from the first day of training. The results show changes in the electrophysiological responses in concert with improving behavioral discrimination, suggesting that the activity is related to grammar acquisition.